Five-dimensional neuroimaging: Localization of the time–frequency dynamics of cortical activity - Dalal, Sarang S.; Guggisberg, Adrian G.; Edwards, Erik; Sekihara, Kensuke; Findlay, Anne M.; Canolty, Ryan T.; Berger, Mitchel S.; Knight, Robert T.; Barbaro, Nicholas M.; Kirsch, Heidi E.; Nagarajan, Srikantan S. (NeuroImage (Orlando, Fla.), 2008)
The spatiotemporal dynamics of cortical oscillations across human brain regions remain poorly understood because of a lack of adequately validated methods for reconstructing such activity from noninvasive electrophysiological data. In this paper, we present a novel adaptive spatial filtering algorithm optimized for robust source time–frequency reconstruction from magnetoencephalography (MEG) and electroencephalography (EEG) data. The efficacy of the method is demonstrated with simulated sources and is also applied to real MEG data from a self-paced finger movement task. The algorithm reliably reveals modulations both in the beta band (12–30 Hz) and high gamma band (65–90 Hz) in sensorimotor cortex. The performance is validated by both across-subjects statistical comparisons and by intracranial electrocorticography (ECoG) data from two epilepsy patients. Interestingly, we also reliably observed high frequency activity (30–300 Hz) in the cerebellum, although with variable locations and frequencies across subjects. The proposed algorithm is highly parallelizable and runs efficiently on modern high-performance computing clusters. This method enables the ultimate promise of MEG and EEG for five-dimensional imaging of space, time, and frequency activity in the brain and renders it applicable for widespread studies of human cortical dynamics during cognition.